2015
DOI: 10.1159/000441978
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Leucine Zipper-Like Motif of the Human Parainfluenza Virus 3 Fusion Protein Impair Fusion Activity

Abstract: Objective: To investigate the effect of the leucine zipper-like motif between HRA and HRB of the human parainfluenza virus 3 fusion protein on fusion activity. Methods: Site-directed mutagenesis was utilized to substitute the heptadic residues at 257, 264, 271, 278, 285, 292, and 299 in this motif with alanine. Additionally, 3middle heptadic leucine residues at 271, 278, and 285 were replaced with alanine singly or in combination. A vaccinia virus-T7 RNA polymerase transient expression system was employed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…To clarify this, point mutations were introduced to substitute the first two heptadic leucines at residues 248 and 255 into prolines (p15RS L248P/L255P ) or alanines (p15RS L248A/L255A ) ( Fig. 2B) (26,27). An immunostaining experiment showed that both mutants were located in the nucleus, similar to the WT p15RS ( Fig.…”
Section: Mutation Of the Leucine Zipper-like Motif Impairs P15rs Dimementioning
confidence: 91%
“…To clarify this, point mutations were introduced to substitute the first two heptadic leucines at residues 248 and 255 into prolines (p15RS L248P/L255P ) or alanines (p15RS L248A/L255A ) ( Fig. 2B) (26,27). An immunostaining experiment showed that both mutants were located in the nucleus, similar to the WT p15RS ( Fig.…”
Section: Mutation Of the Leucine Zipper-like Motif Impairs P15rs Dimementioning
confidence: 91%